Peningkatan Kapasitas Kader Kesehatan dalam Penanganan Kegawatdaruratan melalui Edukasi Pertolongan Pertama Berbasis Usia - Karina Nilasari; Putri Kusuma Cahyaning Gusti Rohmatillah Asfandi; Nuramaliah Desliani Putri; Syarifa Nadia (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Health cadres serve as vital front-liners in primary healthcare, especially as first responders when medical emergencies occur within the community. Yet, many of them still lack the necessary knowledge and confidence to deliver appropriate first aid, which can lead to delayed or incorrect actions. This community engagement program was designed to strengthen their capacity through age-specific first aid education tailored for infants, children, adolescents, adults, and the elderly. The training took place at Bumiaji Public Health Center, Batu City, and involved 80 selected health cadres. Conducted over one day, the program combined interactive lectures, demonstrations, group discussions, and pre- and post-training evaluations. The results showed a significant improvement in knowledge, with the mean error score decreasing from 5.66 to 1.94 (p < 0.001). Participants also expressed increased confidence in recognizing emergency signs and providing timely interventions. These findings highlight that even short, well-structured, and contextually relevant educational activities can substantially enhance community health workers’ readiness to act during emergencies. Replicating such programs in other regions could help strengthen community-based emergency preparedness and contribute to broader efforts in building resilient and responsive primary healthcare systems in Indonesia.